Description of Pericelis flavomarginata sp. nov. (Polycladida: Cotylea) and its predatory behavior on a scaleworm - Tsuyuki, Aoi; Oya, Yuki; Jimi, Naoto; Kajihara, Hiroshi (Zootaxa, 2020)
We describe a new species of polyclad flatworm, Pericelis flavomarginata sp. nov., from the intertidal and subtidal zones along localities on the Pacific coast of Japan. Pericelis flavomarginata sp. nov. is characterized by i) the dorsal surface of the body fringed by a lemon-yellow line except for the tip of tentacles, with a narrow brown midline running from the anterior edge of the body to the posterior end of the pharynx, ii) the pair of marginal tentacles with the tips extending and tapering, and iii) the presence of a common gonopore. Our molecular phylogenetic analysis revealed that selected Pericelis species were divided into two clades, each of which may be agreed with a characteristic dorsal color pattern. Additionally, we report an observation on the feeding behavior of P. flavomarginata sp. nov. on the polychaete Iphione muricata (Savigny in Lamarck, 1818).